Business basics for dentists - Willis, David O. (John Wiley & Sons Ltd., 2013)
Dr. David Willis combines his experience as a practicing dentist, educator, MBA, and certified financial planner in this breakthrough text about managing a dental business. Rather than a checklist of steps for success, Business Basics for Dentists describes business, economic, marketing, and management principles and explains how to apply them to the dental practice. Dental students and new practitioners will learn how to use the core strategic and operational business philosophies to develop an effective dental practice. He provides the essential elements of a business course--management principles, economics, business finance, and financial analysis--without bogged down in too much detail. These are then related specifically to various aspects of running and managing a dental practice, including office communications, billing, inventory, and marketing the practice. All aspects of practice transition are approached: career opportunities, buying a practice, starting a new practice, multi-practitioner arrangements, practice valuation, and planning and developing a practice. Last, Willis included personal financial planning to ensure that the dentist is also planning for his own finances and retirement beyond the bounds of the practice.